PANCHAYATI RAJ AND WOMEN EMPOWERMENT: A SOCIOLOGICAL STUDY OF JIND DISTRICT, HARYANA - Kumar, Sandeep; Joginder; Malik, Naveen; Singh, Kulvir (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Panchayati Raj system is an important pillar of Indian democracy, which promotes rural development and public participation in governance. This study presents a sociological analysis of the status of women empowerment through Panchayati Raj in 10 villages of Jind district of Haryana. The aim of the study is to understand the extent to which women representation in panchayats has affected their social, economic and political status. The experiences of women Sarpanchs and Panchs in the selected villages, the challenges they face, and their contributions were studied using research tools such as interviews and field observations. The results show that women reservation has brought women into panchayats, but patriarchal mindsets, lack of education, and social pressures still limit their effectiveness. However, many women representatives are becoming aware of their roles and are actively participating in the decision-making process. The study concludes that Panchayati Raj has played an important role in empowering women, but policy reforms, training programs, and awareness campaigns are needed to make it more effective. It is necessary to strengthen community and government efforts to eliminate gender-based inequalities at the rural level and make women empowered citizens.